Left Handed Maxwellian Nature of Nano-Structured Layered Material-Mica - Sarkar, Aditi; Gangopadhyay, Arnab; Sarkar, A. (Asian Journal of Chemistry, 2011)
In this work, material aspects of natural mica are studied. This work makes an attempt to analyze the dielectric properties of mica. Several investigations have been carried out on natural mica specimens such as optical absorbance, AC and DC electrical characteristics. Optical reflectance of mica sheet with plane polarized monochromatic light shows distinct difference with conventional theoretical result. The AC and DC conductivities are also measured. There exists a clear difference in DC characteristic for presence and absence of stray electromagnetic fields. The XRD and impedance spectroscopy analysis are also carried out for further analysis. The results obtained from the optical reflectance characteristics using polarized light indicate LHM behaviour as may be found in a meta-material on white mica. However black mica exhibits no such nature. Micro-structural and electrical analysis shows that it is a nano-structured layered material.